Lulu and the Duck in the Pack - McKay, Hilary (UK, 2011)
When Lulu finds a duck egg that has rolled out of its nest, she takes it to class to keep it safe. Lulu isn't allowed to bring pets to school. But she's not really breaking the rules because it's just an egg. Surely nothing bad will happen...
Keywords: Animal Stories; Friendship; Juvenile Fiction